2023
DOI: 10.7759/cureus.35519
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Adult Tuberculosis Patients Admitted to a Rural Hospital in Ethiopia

Abstract: BackgroundEthiopia is one of the countries in the world with the highest rate of tuberculosis (TB). The aim of this study is to describe the characteristics of the patients with TB admitted to a rural hospital in Ethiopia in terms of both diagnosis and clinical management. MethodsA retrospective descriptive observational study was conducted. Data were collected from patients older than 13 years who were admitted to the Gambo General Hospital for TB between May 2016 and September 2017. The variables studied wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In Ethiopia, people diagnosed with TB with mild or no symptoms of TB have a better outcome from screening based on chest radiography. 14 16 When chest X-ray TB screening was used in the country’s first national population-based TB prevalence survey, more than 50% of confirmed TB cases were identified using chest X-ray screening. 17 A facility-based cross-sectional study conducted in Ethiopia on the impact of early chest radiography on delay in pulmonary TB case notification showed that early screening using chest X-ray minimized delays in the diagnosis of pulmonary TB among people with coughs of any duration.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, people diagnosed with TB with mild or no symptoms of TB have a better outcome from screening based on chest radiography. 14 16 When chest X-ray TB screening was used in the country’s first national population-based TB prevalence survey, more than 50% of confirmed TB cases were identified using chest X-ray screening. 17 A facility-based cross-sectional study conducted in Ethiopia on the impact of early chest radiography on delay in pulmonary TB case notification showed that early screening using chest X-ray minimized delays in the diagnosis of pulmonary TB among people with coughs of any duration.…”
Section: Introductionmentioning
confidence: 99%